1977
DOI: 10.1002/bbpc.19770811111
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchung der Fehlordnung von TiO2 (Rutil) mit Hilfe von Leitfähigkeits‐ und Überführungsmessungen

Abstract: Die Abhängigkeit der elektrischen Leitfähigkeit des Rutils vom Sauerstoffpartialdruck ergibt im Exponenten der Beziehung ∑ ∼ po2−1x für x Werte zwischen 4,24 und 4,7. Überführungsmessungen nach der Tubandtschen Methode bei niedrigen Sauerstoffpartialdrücken zeigen eine zur hindurchgeschickten Elektrizitätsmenge proportionale Gewichtszunahme des Kathodenraumes, der eine äquivalente Gewichtsabnahme des Anodenraumes entspricht, was auf Fehlordnung des Kationenteilgitters hinweist.—Die aus der Temperaturabhängigke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Effect of Oxygen Activity. The literature reports on electrical properties of TiO 2 at elevated temperatures concentrate on the effects of oxygen activity and temperature on the electrical properties, including electrical conductivity, thermoelectric power, and Hall effect. However, the vast majority of the reported data concerns the electrical conductivity.…”
Section: Brief Literature Overviewmentioning
confidence: 99%
“…Effect of Oxygen Activity. The literature reports on electrical properties of TiO 2 at elevated temperatures concentrate on the effects of oxygen activity and temperature on the electrical properties, including electrical conductivity, thermoelectric power, and Hall effect. However, the vast majority of the reported data concerns the electrical conductivity.…”
Section: Brief Literature Overviewmentioning
confidence: 99%
“…(iv) what the extent of the ionic contribution to the total conductivity is. 13,[28][29][30] In our earlier work on undoped single crystal TiO 2Àd , 5 we have found that the oxide remains oxygen-deficient all the way up to a O 2 = 1 with the majority type of disorder changing…”
Section: Introductionmentioning
confidence: 94%
“…Most of the reported data on the properties of TiO 2 correspond to the operational equilibrium . The related properties, such as the absolute values of the electrical conductivity, may differ substantially. The difference is related to different oxygen activity in the oxide lattice and the associated concentration of titanium vacancies. The properties of TiO 2 exhibit reproducible properties only when the studied specimens are in full equilibrium.…”
Section: Brief Overview Of Literature Datamentioning
confidence: 99%